ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA DI PROVINSI BALI - ndakularak, erwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.NO.03.TAHUN 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 ABSTRACT Development undertaken by the central and local governments sometimes do not fit or are not in line with the actual needs of society, giving rise to declining public welfare.This research analyzes the factors that affect the public welfare district / city in the province of Bali, either simultaneously or partially. The data used are secondary data sampling method using saturated sampling because the entire population was used as the sample of nine districts / municipalities in the province of Bali as well as using multiple linear regression analysis with the F test and t test. Keywords: Public Welfare and Household Consumption